The global environmental paw print of pet food. (November 2020) - Alexander, Peter; Berri, Aiden; Moran, Dominic; Reay, David; Rounsevell, Mark D.A.
Highlights: Economic value allocation approach to account for animal by-products. Global pet food associated with 56–151 Mt CO2 eq, 1.1–2.9% of agricultural total. Global pet food associated with 41–58 Mha agricultural land-use, 0.8–1.2% of total. Global pet food associated with 5–11 km 3 freshwater use, 0.2–0.4% all agriculture. Pet food should be included in wider food sustainability agenda and research. Abstract: Global pet ownership, especially of cats and dogs, is rising with income growth, and so too are the environmental impacts associated with their food. The global extent of these impacts has not been quantified, and existing national assessments are potentially biased due to the way in which they account for the relative impacts of constituent animal by-products (ABPs). ABPs typically have lower value than other animal products (i.e. meat, milk and eggs), but are nevertheless associated with non-negligible environmental impacts. Here we present the first global environmental impact assessment of pet food. The approach is novel in applying an economic value allocation approach to the impact of ABPs and other animal products to represent better the environmental burden. We find annual global dry pet food production is associated with 56–151 Mt CO2 equivalent emissions (1.1%−2.9% of global agricultural emissions), 41–58 Mha agricultural land-use (0.8–1.2% of global agricultural land use) and 5–11 km 3 freshwater use (0.2–0.4% of water extraction of agriculture). These impacts are equivalent to an environmental footprint of around twicethe UK land area, and would make greenhouse gas emission from pet food around the 60th highest emitting country, or equivalent to total emissions from countries such as Mozambique or the Philippines. These results indicate that rising pet food demand should be included in the broader global debate about food system sustainability.